Selective TRAIL‐induced cytotoxicity to lung cancer cells mediated by miRNA response elements. (1st August 2014) - Wu, Guodong; Ji, Zhiyong; Li, Haifeng; Lei, Yu; Jin, Xiaoyuan; Yu, Yingqing; Sun, Mingli
<x xml:space="preserve">Abstract</x> Lung cancer is among the most common cancers, and the current therapeutic strategies are still inefficient in most cases. Tumour necrosis factor‐related apoptosis‐inducing ligand (TRAIL) is a promising biological agent for cancer treatment because of its potent pro‐apoptotic effect on cancer cells. However, TRAIL also induces apoptosis in normal cells and therefore may cause toxicity to normal tissues if clinically applied. To address this issue, we inserted microRNA response elements (MREs) of miR‐133a, miR‐137 and miR‐449a, which are all underexpressed in lung cancer cells, into an adenoviral vector to regulate TRAIL expression. This MRE‐regulated vector (Ad‐TRAIL‐MRE) was able to express TRAIL in a lung‐cancer‐specific fashion. No TRAIL expression was detected in normal cells. Consistently, Ad‐TRAIL‐MRE exerted cytotoxicity to lung cancer cells, rather than normal cells, perhaps via inducing selective apoptosis. The selective TRAIL‐mediated growth‐inhibiting effect was further confirmed in a tumour xenograft model. Also, Ad‐TRAIL‐MRE only resulted in very low hepatotoxicity when applied. Collectively, we generated a novel TRAIL‐expressing adenoviral vector that was regulated by MREs. This strategy permits TRAIL expression in a lung‐cancer‐specific manner and is worth further studying for clinical trials. Copyright © 2014 John Wiley & Sons, Ltd.